2021
DOI: 10.11604/pamj.2021.38.250.19790
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic determinants of glycaemic control among children with type 1 diabetes in South Eastern Nigeria

Abstract: Introduction diabetic complications have been identified as the major causes of morbidity and mortality in persons with type 1 diabetes mellitus (T1DM). Lack of appropriate glycaemic control is a significant risk factor for the onset and progression of long term complications of diabetes. Identifying the determinants of good glycaemic control is therefore imperative. Methods this was a cross-sectional, hospital-based study of children aged 3-18 years with T1DM. Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…This is in line with study done in Southeast Nigeria, on sociodemographic determinants of glycemic control among children with type 1 diabetes, and found caregivers’ involvement in diabetes management was the only strong determinant for optimal glycemic control. 8 This could be explained by some children may not take doses accurately when they take without supervision by the caregiver.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in line with study done in Southeast Nigeria, on sociodemographic determinants of glycemic control among children with type 1 diabetes, and found caregivers’ involvement in diabetes management was the only strong determinant for optimal glycemic control. 8 This could be explained by some children may not take doses accurately when they take without supervision by the caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…It is also consistent with the finding of study done in Sudan which showed the prevalence of poor glycemic control of 76%. [7][8][9]11,16 This similarity in glycemic control could be due to the same poor socioeconomic status in these countries as poor socioeconomic status contributes to poor glycemic control through its undesired effects on quality of diabetes care, treatment adherence, and provision of adequate and healthy nutrition. 17 According to this study regarding the nutritional status of children and adolescents with diabetes, about 22.2% were stunted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations